Chapter 16: Image control and public attitudes - Hrast, Maša Filipovič (Edward Elgar Publishing, 2024)
The way images of homeless(ness) are created is a complex matter where the views of different actors compete and coexist. This chapter considers the different actors included in the process of image creation, from researchers, to policymakers, service providers and the media. These images not only influence each other, but also shape public perception of, and attitudes towards homelessness. The chapter examines the gendered and medicalised image of homelessness and how it is linked to certain solutions (policy and services) that seek to change individual behaviour. Furthermore, the chapter discusses the formation of public attitudes and how they are linked to perceptions of the deservingness of vulnerable groups, which in turn can affect public support for various policies aimed at assisting people experiencing homelessness.